Contribution to the modeling of a pneumatic semi-active control of vehicle suspension - Khettou, Nabil S.; Demić, Miroslav M.; Muždeka, Slavko R.; Krsmanović, Milan M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
This paper contributes to the modeling of a semi-active control of a quarter vehicle model using air springs. A conventional mass-spring-damper model has been used along with an air spring. Based on the theory of thermodynamics, the dynamic equation of the air springmodelwas established. The simulation model was implemented using MATLAB and the transfer functions with varying parameters were calculated. The simulation results show that air spring pressure, the valve diameter, the dumping coefficient and the mechanical stiffness affect the dynamic response of the system. A semi-active control methodology was then established by controlling the valve diameter using two declinations of an on-off logic switch based on the velocity of the suspended mass and the relative velocity at both ends of the air spring. The obtained results show reduced oscillation amplitudes around the natural frequency of the system.
Keywords: air spring; suspensions; Pneumatics; Vehicles